Spatial Organization of Economic Development of Energy Resources in the Arctic Region of the Russian Federation - AGARKOV, Sergey Anatolievich; KOZMENKO, Sergey Yurievich; SAVELIEV, Anton Nikolaevich; ULCHENKO, Mikhail Vasilyevich; SHCHEGOLKOVA, Asya Aleksandrovna (Journal of Environmental Management and Tourism, 2018)
In the conditions of price reduction in the world energy market, the issue of determining the priorities of the economic development of hydrocarbons in the Arctic Region of the Russian Federation (RF) becomes highly relevant. The article is aimed at developing an optimal model for the spatial organization of energy resources in the Arctic Region. The expert elicitation procedure was used to determine the efficiency indicators for the economic development of the oil-and-gas-bearing areas in the Arctic Region and clusterization of these areas was carried out in terms of economic efficiency. Based on the factor analysis, the degree of influence of efficiency indicators on the economic development of the oil and gas bearing areas of the region was determined and, an integrated performance indicator of economic development for oil-and-gas-bearing areas for each cluster was calculated with regard to the factor loadings. A 3-D model was developed for the organization of economic development of oil and gas in the Arctic Region. The 3-D model became the basis for determining the priorities for territorial exploration, development and production of hydrocarbons in terms of their economic efficiency, taking into account the trends in the development of the world energy market and break-even fields. A set of recommendations was developed to improve the efficiency of the spatial organization of economic development of oil and gas in the Arctic Region. The implementation of the proposed measures can contribute to the development of the oil and gas industry in the region, its socio-economic development and the long-term sustainability of Russia's energy security.